2014 WSGC Elijah High-Altitude Balloon Payload Project - Jadee, Kellog; Lambert, Madeline; Ochoa, Danny; Schilling, Evan; Stefik, Michael; Wiznitzer, Michael (Proceedings of the Wisconsin Space Conference, 2015)
The purpose of this paper is to discuss the development and findings of the experiments performed on the high altitude balloon payload. After some bonding time in the beginning of the summer, the team got together and decided on the four following experiments: Atmospheric Electric Field, Breakdown Voltage, IR Imaging, and Solar Efficiency/Payload Spin. Subsequently, research and fabrication began which involved learning new skills such as Arduino programming, 3-D modeling, foam cutting, and more. The launch was successful, and the results retrieved were more or less what were expected. This internship opportunity proved to be an amazing learning experience for the team which will be valued for each of their future career experiences.